Pinocchio - Fior, Jane; Bartram, Simon (Illustrator) (Orlando, Florida: Family learning, from Dorling Kindersley Pub., 1999)
A retelling of the adventures of Pinocchio, a mischievous wooden puppet, who wants more than anything else to become a real boy. Illustrated notes throughout the text explain the historical background of the story.
Keywords: English, Fiction, Fairytales